1993
DOI: 10.1038/clpt.1993.25
|View full text |Cite
|
Sign up to set email alerts
|

A potentially hazardous interaction between erythromycin and midazolam

Abstract: Interaction between erythromycin and midazolam was investigated in two double-blind, randomized, crossover studies. In the first study, 12 healthy volunteers were given 500 mg erythromycin three times a day or placebo for 1 week. On the sixth day, the subjects ingested 15 mg midazolam. In the second study, midazolam (0.05 mg/kg) was given intravenously to six of the same subjects, after similar pretreatments. Plasma samples were collected, and psychomotor performance was measured. Erythromycin increased the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
76
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(80 citation statements)
references
References 0 publications
4
76
0
Order By: Relevance
“…In vitro data indicate that midazolam metabolism is inhibited by many other drugs (Gascon and Dayer 1991). We have previously shown that erythromycin distinctly alters the pharmacokinetics of midazolain and potentiates the psychomotor actions of midazolain hazardously (Olkkola et al 1993). Now, using the same study design, the effect of roxithromycin on the pharmacokinetics of midazolam proved to be clearly smaller than the effect of erythromycin and appeared less likely to lead to clinically significant changes in the pharmacodynamics of midazolam.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In vitro data indicate that midazolam metabolism is inhibited by many other drugs (Gascon and Dayer 1991). We have previously shown that erythromycin distinctly alters the pharmacokinetics of midazolain and potentiates the psychomotor actions of midazolain hazardously (Olkkola et al 1993). Now, using the same study design, the effect of roxithromycin on the pharmacokinetics of midazolam proved to be clearly smaller than the effect of erythromycin and appeared less likely to lead to clinically significant changes in the pharmacodynamics of midazolam.…”
Section: Discussionmentioning
confidence: 84%
“…The macrolide antibiotic erythromycin inhibits the metabolism of midazolam in vitro and also in humans (Byatt et al 1984;Gascon and Dayer 1991;Hiller et al 1990). In a previous study erythromycin treatment increased the area under the midazolam concentration-time curve more than four-fold and peak midazolam concentration almost three-fold after a 15-mg oral dose of midazolam, which caused more proPresented in part at the 18 th International Congress of Chemotherapy, Stockholm, Sweden, June 27-July 2, 1993 Correspondence to: J. T. Backman, Department of Clinical Pharmacology, University of Helsinki, Paasikivenkatu 4, SF-00250 Helsinki, Finland found and prolonged psychomotor effects (Olkkola et al 1993).…”
mentioning
confidence: 99%
“…The latter is a second reaction, which has been proposed as a measure of the in vivo function of CYP3A4 (7). The ability of macrolide antibiotics, such as erythromycin, to influence the pharmacokinetics of other drugs is exemplified by the recent report (33) of the "undesirably severe and excessively longlasting hypnotic effects" seen when young adults were pretreated with erythromycin prior to oral administration of the 1,4-benzodiazepine short-acting hypnotic agent midazolam. Midazolam is metabolized by P450 3A4 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Erythromycin administed orally for one week [7] inhibited the hepatic metabolism of midazolam, leading to an increase in its plasma concentrations and enhancement of its effects. Even single oral doses of erythromycin 750 mg have increased the plasma level of midazolam and enhanced its effects on human psychomotor performance [8].…”
mentioning
confidence: 99%